2022
DOI: 10.1021/acs.accounts.2c00063
|View full text |Cite
|
Sign up to set email alerts
|

Biomineral-Inspired Colloidal Liquid Crystals: From Assembly of Hybrids Comprising Inorganic Nanocrystals and Organic Polymer Components to Their Functionalization

Abstract: Conspectus Bioinspired organic/inorganic synthetic composites have been studied as high-performance and functional materials. In nature, biominerals such as pearls, teeth, and bones are self-organized organic/inorganic composites. The inorganic components are composed of calcium carbonate (CaCO 3 ) and hydroxyapatite (HAp), while the organic components consist of peptides and polysaccharides. These composites are used as structural materials in hard biological tissues. Biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Unsymmetrical cores, unlike conventional organic materials, enable the arrangement of molecules in the solid state not only by π–π interactions but also by dipole‐dipole interactions. If flexible alkyl groups are introduced into the rigid unsymmetrical cores, the unsymmetrical complexes can be applied to new metallomesogens, which can provide various molecular liquid crystals exhibiting multifunctionalities [33–36] . Because of their unconventional electronic states, unsymmetrical metal‐dithiolene complexes with flexible alkyl groups can also be good candidates for new components that provide multifunctional liquid crystals exhibiting conducting and/or optical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsymmetrical cores, unlike conventional organic materials, enable the arrangement of molecules in the solid state not only by π–π interactions but also by dipole‐dipole interactions. If flexible alkyl groups are introduced into the rigid unsymmetrical cores, the unsymmetrical complexes can be applied to new metallomesogens, which can provide various molecular liquid crystals exhibiting multifunctionalities [33–36] . Because of their unconventional electronic states, unsymmetrical metal‐dithiolene complexes with flexible alkyl groups can also be good candidates for new components that provide multifunctional liquid crystals exhibiting conducting and/or optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…If flexible alkyl groups are introduced into the rigid unsymmetrical cores, the unsymmetrical complexes can be applied to new metallomesogens, which can provide various molecular liquid crystals exhibiting multifunctionalities. [33][34][35][36] Because of their unconventional electronic states, unsymmetrical metal-dithiolene complexes with flexible alkyl groups can also be good candidates for new components that provide multifunctional liquid crystals exhibiting conducting and/or optical properties. Based on this strategy, we synthesized unsymmetrical platinum(II) and gold(III) complexes coordinated by a dithiolene ligand containing the TTF moiety with flexible decylthio groups,…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The components with anisotropic shapes of particles form ordered and mobile assembled states. Recently we reported that biomineralization-inspired colloidal liquid crystals were formed based on calcium carbonate (CaCO 3 ) 13,14 and hydroxyapatite [15][16][17][18] particles complexed with an acidic macromolecule, poly(acrylic acid) (PAA). For hydroxyapatitebased liquid crystals, stimuli responsive properties and biofunctions, e.g., magnetic eld responsive colloidal liquid crystals composed of nanorods, were reported.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In a typical biomineralization process, inorganic crystals are complexed with biomacromolecules to afford structural materials in hard biological tissues. 27 Nevertheless, a massive amount of effort is required to understand the integrating mechanism of biomineralization. On the contrary, certain functionalities, e.g., mechanical, optical, and electric properties, require the formation of highly ordered structures, which, however, is still challenging because it requires delicate tuning of interphase attractions.…”
mentioning
confidence: 99%
“…The complexation of organic and inorganic components offers approaches for integrating the enriched functionalities of inorganic materials with the excellent flexibility and processability of polymers. , The covalent/noncovalent interactions between the two phases can be tuned for the controlled formation of hierarchical structures. , In a typical biomineralization process, inorganic crystals are complexed with biomacromolecules to afford structural materials in hard biological tissues . Nevertheless, a massive amount of effort is required to understand the integrating mechanism of biomineralization.…”
mentioning
confidence: 99%